(untitled) (Bangladesh Journal of Agricultural Research, 2019)
Conservation agriculture (CA) with appropriate nutrient management can help increase crop production, improve soil health and bring economic return. An experiment was conducted at farmer’s field of Rajbari district under Low Ganges River Floodplain (AEZ-12) during 2017-2018 to evaluate the effects of tillage and nutrient management on the system productivity and profitability in the jute - T. Aman rice- onion cropping system. Strip tillage (ST) for jute, non-puddling for T. Aman rice and one pass minimum tillage (MT) for onion was contrasted with conventional crop establishment practice (CT). Four different nutrient management practices were NM1: farmer’s practice (FP), NM2: soil test based (STB) fertilizer, NM3:25% extra of STB and NM4: organic amendments (20 % nutrients from cowdung). The experiment was laid out in a split-plot design with three replications by assigning tillage practices in main plots and nutrient management in sub-plots. The yield attributes of jute, T. Aman rice and onion responded similarly to tillage practices. On the other hand, the system productivity and yield of component crops varied due to different nutrient management practices (p<0.05). The highest fibre yield of jute (3.64 t ha-1) was obtained in 25% extra of STB fertilizer dose; the highest T. Aman yield (6.02 t ha-1) and the highest onion bulb yield (16.0 t ha-1) in 20 % organic nutrient management, followed by25 % extra of STB fertilizer dose. The highest system productivity was also produced by 20 % organic amendments (33.6 t ha-1), followed by 25 % extra of STB fertilizer dose (32.3 t ha-1). The lowest yield of crops and system productivity was recorded in FP (28.6 t ha-1).The increased yield of T. Aman rice and onion in 20 % organic amendment by cowdung and ST resulted in the highest net return (NR) and benefit-cost ratio (BCR), while 25% extra of STB and FP under CT gave the lowest NR and BCR. Residual nutrient from successive use of cowdung combined with chemical fertilizers outperformed other management practices in terms of crop yield and economic return. Bangladesh J. Agril. Res. 44(3): 387-399, September 2019